Provision of Contraceptive Implants in School-Based Health Centers: A Cost-effectiveness Analysis. Issue 3 (March 2021) - Kim, Chi-Son; Lunde, Britt; MacIsaac, Laura; Arden, Martha; Garney, Whitney R.; Wilson, Kelly L.; Li, Yan
Abstract : (Abstracted from Contraception 2021;103(2):107–112) Among high-income countries, the United States has the highest rate of teen pregnancy. Most teen pregnancies are unintended.